Effect of Aging on the Microstructure and Optical Properties of Translucent ZrO 2 Ceramics - Korina Mešić; Igor Majnarić; Ketij Mehulić (University of Zagreb. School of Dental Medicine, 2021)
Objectives: The development and placement of translucent zirconia ceramics on the dental materials market is in full swing. This research aimed to investigate how aging protocols affect the microstructure, color parameters and translucency of a new-generation monolithic zirconia ceramic. Material and methods: Translucent zirconia ceramics KATANA-Zirconia STML with different surface treatments (as sintered - control, glazed, polished) was tested using two aging protocols (hydrothermal degradation in autoclave at 134 °C and 2 bars for three hours, chemical degradation in four-percent acetic acid at 80 °C for 16 hours) in order to examine phase composition using X-ray diffraction analysis and ΔE, ΔL and ΔC color parameters through spectrophotometry. The translucency parameter (TP) was calculated using parameters L*, a* and b* on a black and white surface. Results: Regardless of the surface treatment, aging protocols did not cause a tetragonal-to-monoclinic phase transformation, although hydrothermal degradation in the autoclave transformed the hybrid tetragonal-cubic structure of all specimens to a tetragonal one. All polished and glazed specimens during chemical degradation demonstrated a significant color change ΔE. Lightness ΔL significantly changed in polished specimens aged in the autoclave. In all specimens, ΔC underwent a change manifested through statistically insignificant yellowing. None of the aging protocols altered the translucency of specimens. Conclusions: Aging, regardless of the final surface treatment, did not manifest a monoclinic phase in the specimens. A tetragonal-cubic microstructure dominates. Unlike polishing, glazing the surface of translucent zirconia ceramics contributed to minor changes in color, lightness and chromaticity. The translucency of translucent zirconia ceramics remains stable regardless of aging and surface treatment.